Pengaruh Likuiditas, Solvabilitas dan Aktivitas Terhadap Profitabilitas Pada PT. KDB Tifa Finance Tbk Periode 2015-2025 - Ridzal Muhammad Bidzaksana; Novianti Ayu Lesmanah; Siti Habibah; Jelita Zahrani Fadhila; Devandito Nandika Putra; Fazhar Sumantri (Journal Of Business, Finance, and Economics (JBFE), 2026)
This study investigates the impact of liquidity, solvency, and activity ratios on the profitability of PT KDB Tifa Finance Tbk between 2015 and 2025. Utilizing a quantitative methodology with descriptive and confirmatory elements, data was gathered through purposive sampling and documentation. The analytical framework consisted of classical assumption tests, multiple linear regression, and hypothesis testing. The findings reveal that: (1) liquidity (CR) does not individually influence profitability (ROA); (2) solvency (DER) exerts a significant partial effect on ROA; (3) activity (TATO) shows no significant standalone impact on profitability; and (4) when combined, liquidity, solvency, and activity levels collectively determine the company’s profitability.